Evidence for the ambiguity of the term constipation: the role of irritable bowel syndrome. Issue 10 (October 1994) - Probert, C S; Emmett, P M; Cripps, H A; Heaton, K W
Abstract : A satisfactory definition of constipation is elusive. An important and measurable element is slow colonic transit. Whole gut transit time, a proxy for colonic transit time, can be estimated from self recorded data on stool form and frequency. Our aim was to compare whole gut transit time with subjective definitions in the context of the general population. In a community based sample of 731 women aged 25-69 years the estimated whole gut transit time was compared with two subjective assessments of constipation-the woman's own perception and a symptom based definition proposed by an international working team (Rome definition). We have defined slow whole gut transit time as > 2 SD above the mean in women who seldom passed lumpy stools (that is, > 92 hours). Slow transit was present in 9.3% of the sample. Similar numbers met the subjective definitions (8.5% and 8.2%). However, the overlap between the three definitions was poor. Of 68 women with estimated slow transit, 28 had self perceived constipation, 20 had Rome defined constipation, and only 11 had both. Of subjects classified as constipated by the subjective definitions only 37% had slow transit; they had a high prevalence of irritable bowel symptoms. In conclusion, this study showed that the term constipation is ambiguous and often misleading and that attempts to base a definition on symptoms are misguided. In epidemiological studies, conclusions about the prevalence of constipation should be based on records of stool type and timing.